Penggunaan Media “Layar Putar” pada Pembelajaran Tematik Siswa Tuna Rungu - Rahmi, Firlia (Jurnal Didaktika Pendidikan Dasar, 2021)
“Layar Putar” media is designed to help deaf students in thematic learning in elementary school. Students with disabilities who are deaf need media in the learning process. Media that are designed in addition to being interesting can also concretize abstract subject matter. “Layar Putar” is a television-like medium in which there are images. The “Layar Putar” learning media is designed to help deaf students understand the content of Indonesian and natural science lessons. In Indonesian language there is about writing poetry. In the science lesson the material delivered by the teacher is about the life cycle of animals. The study was conducted on one disability student in SD Negeri 1 Banda Aceh as one of the inclusive schools. Research data collection using the initial test and final test. The media “Layar Putar” is disseminated to the teacher in providing learning for students with special needs. The “Layar Putar” media can be used as a learning medium for deaf students with disabilities. Development of "“Layar Putar” media using the ADDIE model. The ADDIE model starts with analyzing, designing, testing validation at the design stage, implementing it on the subject of research focus, and evaluating the use of media. The results showed that the “Layar Putar” media can be used by deaf students as a medium of learning Indonesian Language and Science which is quite effective.